An assessment of the climatic suitability of Namibia for tourism using the Tourism Climate Index (TCI) - Noome, Kirsten (My University, 2020)
The Tourism Climatic Index (TCI) is the most widely used index to quantify climate suitability for tourism. The wealth of this research is concentrated in the Global North. To date, only a handful of studies have been conducted in southern Africa. This study aims to contribute to closing this gap in tourism-climate research in the Global South. This study presents the application of the TCI in Namibia. The region is heavily reliant on the tourism sector, which primarily comprises outdoor activities, for economic income. Namibian nature-based tourism includes game-viewing and wildlife tours, sight-seeing, cultural visits, climbing, hiking, camping, 4x4 trails and quad-biking. Climatic conditions are often conducive to these activities taking place, and tourist satisfaction. The length of season for these activities and the timing of peak tourist arrivals is mainly reliant on favourable climatic conditions. Rising temperatures, changes in relative humidity and precipitation pose real threats to nature based and adventure tourism in Namibia. The economic reliance of tourism and specific climatic conditions that promote successful tourism in Namibia prompted the use of the TCI. As a result of the latitudinal position of Namibia, the seasonal migration of the Intertropical Convergence Zone (ITCZ), Subtropical High Pressure Zone and southern hemisphere Westerlies influence the climate of the country. The results of the TCI classify Namibia as having ‘good’ to ‘excellent’ climatic conditions for the period 2008–2018. TCI scores for Namibia reveal a bimodal-shoulder and winter peak, meaning the peak climatic conditions are in the austral spring, autumn and winter months. This agrees with the literature regarding peak tourist seasons, which also aligns with school holidays. The spatial and seasonal distribution of climate resources in Namibia derived from the TCI results of this research may greatly assist in positive efforts towards tourism and other economic sectors sensitive to climate.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science (MSc) to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, 2020